Analysis of the influence of workload, communication, and work commitment on employee performance at pt kao Indonesia - Manda Dwipayani Bhastary; Agus Susanto; Wilbert Suhendra Chandra (Enrichment : Journal of Management, 2026)
This This study aims to analyze the influence of workload, communication, and work commitment on employee performance at PT KAO Indonesia, Medan Branch. The underlying phenomenon of this research is the importance of improving employee performance, which is influenced by both internal and external company factors. This study used a quantitative method with an associative approach. The study population was all employees of PT KAO Indonesia, Medan Branch, with a sample of 70 respondents determined using a saturated sampling technique. The results showed that workload had a positive and significant effect on employee performance, communication also had a positive and significant effect on employee performance, and work commitment had a positive and significant effect on employee performance. Simultaneously, workload, communication, and work commitment significantly influenced employee performance, with an F-value of 16.960 > F-table of 2.74 at a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.435 indicates that the variables workload, communication, and work commitment explain 43.5% of employee performance, while the remaining 56.5% is influenced by other factors not examined in this study. The conclusion of this study is that the more proportional the workload, the better the communication, and the higher the work commitment, the higher the employee performance. This research provides implications for companies to continue to pay attention to workload management, improve communication effectiveness, and strengthen employee work commitment to achieve optimal performance